Representações docentes sobre alunos indígenas e as implicações da Lei 11.645/2008 - Farias, Patricia Angelica De Oliveira [UNIFESP] (2019)
From the interviews of six History teachers from two municipal schools in the TI Jaragua surrounding area carried out in the first half of 2018, this paper seeks to understand how the representations that these teachers have of the indigenous populations as a whole impact their pedagogical practices, both in terms of approaches in Indigenous History and in terms of integrating the diverse identities of students in the everyday classroom because, since 2008, we have a Law (11.645 / 2008) that makes the teaching of Indigenous History compulsory and also given the peculiarity of having indigenous students who are enrolled in the schools where the interviewees teach. In this sense, we are theoretically based on Henri Lefebvre's elaborations on Theory of Representations, on the concept of school culture by Dominique Julia (2001), on the ideas of Eliana Monteiro (2011) on the use of the study of ethnographic character as a way of approaching school cultures and working methodologies with oral sources discussed by Michael Pollak (1992) and Alessandro Portelli (1997) to look beyond the first layer of teacher reports. Based on the interviews and the brief ethnographic study, we were able to discuss issues such as the appropriation by teachers interviewed of the debates about the SME / SP curricular construction movement (between the years 2013-2016), the impact of Law 11.645 / 2008 on teaching approaches in relation to Indigenous History and visibility or invisibility of indigenous identities in everyday school.